Contractual scope management of international agencies' funded projects in Afghanistan - Hilali, Ahmadullah; Chotchai Charoenngam; Hadikusumo, Bonaventura H. W.; Santoso, Djoen San; Ministry of Higher Education (MoHE)/Kandahar University, Afghanistan; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2015)
This study is conductedon contractual scope management practices of international agencies in Afghanistan. This study discusses that how the scope of a project canbe managed through using different types of contract considering scope completeness and associated uncertainties. Therefore the major components which are discussed in this research are;1-Scope completeness. 2-Scope pricing.3-Negotiation. In scope completeness scenario it is discussed that scope of a project can be categorized into three parts; a) Complete part, which all contract documents are completed. b) Incomplete part, where the quantity of the work to be undertaken is not cleared at the tendering stage of the project. c) Incomplete part, where the specification or method statement of the work is not cleared.Scope pricing methods are discussed and stated that based on the above three scope completeness scenarios the following three types of the contract can be used; a) Lump Sum for the complete part or scope. b) Re-measurement contract for the scope or part of it where the quantity of the work is not confirmed. c) Provisional Sumcan be used for the part of scope where latent conditions and foreseen works are expected. Negotiation was found as the key for smooth execution of scope management.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Construction, Engineering and Infrastructure Management, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2015
Keywords: Construction contracts -- Management -- Afghanistan; Management contracts -- Afghanistan